Analysis of Body Mass Index with Primary Dismenorrhea Pain Level in Adolescents - Janur Putri (Jurnal Ilmu-Ilmu Kesehatan, 2026)
Dysmenorrhea can have significant negative impacts, affecting a woman's quality of life in carrying out daily activities, decreasing work performance, and academic achievement. Several studies have shown an increased risk of menstrual pain in those who are underweight or overweight. This research This study used a quantitative descriptive research design with a cross-sectional approach. The population in this study were adolescents in Jember Regency. The sample was taken using purposive sampling. The number of samples obtained was 48 respondents. The statistical test used in the bivariate analysis was chi-square. The results of the study showed that 34 respondents (70.8%) had normal nutritional status and 14 respondents (29.2%) had malnutrition. The level of mild dysmenorrhea pain was 13 respondents (27.1%) and the level of moderate dysmenorrhea pain was 35 respondents (72.9%). The results of the statistical analysis of body mass index with the level of primary dysmenorrhea pain in adolescents with a p-value of 0.046 and an OR value of 7.09. Women with a high BMI will have a greater chance of experiencing higher pain severity than normal women. Excess fat tissue causes pressure on blood vessels, thereby disrupting blood flow and resulting in pain during menstruation. Women with a low BMI are assumed to have inadequate nutritional intake during the luteal phase of menstruation, thereby worsening pain during menstruation.